The potential role of patent and proprietary medicine vendors' associations in improving the quality of services in Nigeria's drug shops - Abisoye S. Oyeyemi; Oladimeji Oladepo; Adedayo O. Adeyemi; Musibau A. Titiloye; Sarah M. Burnett; Iorwakwagh Apera (BMC, 2020)
Abstract Background Patent and Proprietary Medicine Vendors (PPMVs) play a major role in Nigeria's health care delivery but regulation and monitoring of their practice needs appreciable improvement to ensure they deliver quality services. Most PPMVs belong to associations which may be useful in improving their regulation. However, little is known about how the PPMV associations function and how they can partner with relevant regulatory agencies to ensure members' compliance and observance of good practice. This study sought to describe the PPMV associations' structure and operations and the regulatory environment in which PPMVs function. With this information we explore ways in which the associations could help improve the coverage of Nigeria's population with basic quality health care services. Methods A mixed methods study was conducted across four rural local government areas (LGAs) (districts) in two Nigerian states of Bayelsa and Oyo. The study comprises a quantitative data collection of 160 randomly selected PPMVs and their shops, eight PPMV focus group discussions, in-depth interviews with 26 PPMV association executives and eight regulatory agency representatives overseeing PPMVs' practice. Results The majority of the PPMVs in the four LGAs belonged to the local chapters of National Association of Patent and Proprietary Medicine Dealers (NAPPMED). The associations were led by executive members and had regular monthly meetings. NAPPMED monitored members' activities, provided professional and social support, and offered protection from regulatory agencies. More than 80% of PPMVs received at least one monitoring visit in the previous 6 months and local NAPPMED was the organization that monitored PPMVs the most, having visited 68.8% of respondents. The three major regulators, who reached 30.0-36.3% of PPMVs reported lack of human and financial resources as the main challenge they faced in regulation. Conclusions Quality services at drug shops would benefit from stronger monitoring and regulation. The PPMV associations already play a role in monitoring their members. Regulatory agencies and other organizations could partner with the PPMV associations to strengthen the regulatory environment and expand access to basic quality health services at PPMV shops in Nigeria.